Digitalisasi Manajemen Bank Sampah Terpadu di Banjar Tegeh Sari, Kelurahan Tonja: Digitalization of Integrated Waste Bank Management in Banjar Tegeh Sari, Tonja Village - Bagus Arya Wijaya; Yudistira Adnyana; Putu Doddy Heka Ardana; I Made Sumada; Cokorda Gede Swetasoma (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Banjar Tegeh Sari, Tonja Village, North Denpasar District, is one of the banjars or groups of residents who have sufficient social capital in waste management. Banjar Tegeh Sari has several activity units directly and indirectly related to waste management, such as waste bank groups, empowered gardens (including bio pore and infiltration wells), and cooperatives. The main problem in waste management at Banjar Tegeh Sari is the need for digitalization and integrated management between the five waste bank groups in Banjar Tegeh Sari and the Manik Galih Cooperative. The aim of integrating and digitizing waste banks is to combine the five groups of waste banks so that recording the amount of non-organic waste becomes more valid and practical while recording the nominal amount of waste in cooperatives. The solution provided is a conceptual model for designing and digitizing waste banks in an integrated manner with cooperatives which will later be called the Tegeh Sari Integrated Waste Management System (SiMaSaDu Tegeh Sari). The target is to integrate and digitize the five waste bank groups into the waste bank management cooperative to make it more efficient and effective.